The Efficiency of Intellectual Capital as a Crucial Factor of Innovation - Béresné Mártha, Bernadett; Lakatos, Vilmos; Tömöri, Gergő (International Journal of Engineering and Management Sciences, 2020)
In today's global economy, there is a substantial shift from manufacturing to services, which challenges both economic policymakers, business stakeholders, owners, suppliers, competitors, and ordinary people: restructuring will encourage all economic players to learn how to adapt to new trends. That is why our research focuses on innovation and the ability of companies to create value. The IT sector is currently one of the fastest-growing and most innovative sectors within the service industry. The success of IT companies is greatly determined by their ability, how to make effective use of their intangible assets at their disposal, including intellectual capital, which is defined as a non-financial asset. So the question may arise: how is it possible to quantify and in monetary terms the intellectual capital of the companies to be examined? That is why, we calculated for the most successful Hungarian IT companies the widely recognized index, the VAICTM index, for which domestic calculations are not yet available. Indeed, this indicator eliminates the lack of information stemming from reporting standards by the methodology relying on publicly available financial reporting data. The indicator itself is a top indicator whose two main sub-indicators quantify the effectiveness of intellectual capital and physical capital.